The biggest or the most abundant? Predation of the black drum pogonias cromis (perciformes, sciaenidae) on benthic organisms in Southern Brazil - Dos Santos, Paulo Roberto Santos [UNESP]; Paiva, Beatriz; Velasco, Gonzalo (Pensoft Publishers, 2019)
Predators that consume larger prey acquire a greater net return of energy per individual, even though they are less abundant. The objective of this work is to analyze the feeding biology of Pogonias cromis in southern Brazil, in order to test for the occurrence of ontogenetic changes in diet as fish reach larger sizes, by consuming larger prey as they grow. Between August 2014 and May 2016, 347 specimens were collected from catches of the fishing fleet that operate in the Patos lagoon estuary and in the adjacent marine area of Cassino beach, that use artisanal fishing gillnets. The prey-specific relative importance index, food overlap, niche breadth and prey length preference were calculated for three length classes, class 1 (27.8–48.73 cm), class 2 (48.73–69.66 cm) and class 3 (69.66–90.60 cm). A total of 13 food items (6 species of crustaceans, 5 species of mollusks, fish fragments and non-animal fragments) were identified, where two species of mollusks (Heleobia australis and Erodona mactroides) represented 90.49% of the diet. The overlap index was moderate between classes 1 and 2, high between 2 and 3 and moderate between 1 and 3. There was a low niche breadth at the population level and for each length class. There were no significant differences in the length of prey consumed among classes. The data obtained here indicates that P. cromis can be classified as a predator specialized in mollusks, with low tendency to ontogenetic changes in southern Brazil. Considering information from the population of P. cromis from Argentina, it can be inferred that the species in the waters of southern South America is a benthic predator adapted to local conditions.
Keywords: Feeding biology; Food overlap; Niche breadth; Ontogenetic changes